Tingkat Kesadaran dan Implementasi manajemen Risiko di Perusahaan Start-up - Samsinar Sinar; Sudarso Kaderi Wiryono (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Digital start-ups have grown rapidly in Indonesia which reached 1.190 total start-ups according to the MIKTI start-up mapping in 2021. However, this growth aligns differently with the success rate since 95% of the start-ups fail. The high failure rate of start-ups indicates that the risk faced by a start-up is high. Therefore, many companies implement risk management because it can help maintain its risk and protect its value. Concerning that issue, the researcher wants to know the level of risk management awareness and implementation in start-up company. To answer that question, the researchers conducted quantitative research and collected the data using non-probability and purposive sampling techniques. The number of respondents is 51, which are CEO/Founder of Digital Start-up in Indonesia. The data collection used an online questionnaire with a close-ended question with three parts: respondent demographic, risk management awareness variable, and risk management implementation variable. The method analysis used is a descriptive to get an overview about risk management awareness level and the implementation. This research shows that the risk management awareness level of digital start-up CEO/Founders is high, but the risk implementation still needs to be fully implemented. Keywords: risk management, start-up, risk awareness